Estimation of Spring Runoff Characteristics of Lowland Rivers in Kazakhstan - ARYSTAMBEKOVA, Dinara; DAVLETGALIEV, Saken; CHIGRINETS, Aleksandr; MUSSINA, Ainur; JUSSUPBEKOV, Daulet (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).19, 2017)
This paper considers the methods and results of determining statistical parameters for spring flood runoff by the main lowland river basins of Kazakhstan for the long-term period. It presents a series of observations made for the long-term period, determines statistical parameters for the depth of spring flood runoff as well as constructs the probability curves of the depth of spring flood runoff by study areas. The paper also gives an estimation of the probability values of the depth of spring flood runoff for the calculation period and for the last period of runoff formation in the context of ongoing climate change. These characteristics are determined by four river basins belonging to the lowland territory of Kazakhstan.